2016
DOI: 10.1007/s10643-016-0815-9
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Positive Family Interactions: Evaluating a Free Early Childhood Book Distribution Program

Abstract: The Dolly Parton Imagination Library (DPIL) program encourages reading among families of preschool children by mailing age-appropriate books, once per month, until the age of five. An evaluation of a DPIL program in a southern state in the U.S. was conducted to assess the impact on enrolled children. Focus groups were conducted and a survey was administered to over 100 parents of children in the program to determine parents' satisfaction withand assessment ofthe program relative to its activities and stated ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…Specifically, less than 15% of students with 0-10 books in their home scored proficient in the 2015 National Assessment of Education Progress versus 50% of students with more than 100 books who scored proficient (US Department of Education, 2021). Children with a larger number of books in their homes tend toward greater gains in academic attainment when compared to their peers with fewer books, especially for less advantaged populations such as parents with less formal education (Funge et al, 2016). Per the Scholastic (2020) report, frequent readers have greater access to books at home and at school.…”
Section: Access By Other Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, less than 15% of students with 0-10 books in their home scored proficient in the 2015 National Assessment of Education Progress versus 50% of students with more than 100 books who scored proficient (US Department of Education, 2021). Children with a larger number of books in their homes tend toward greater gains in academic attainment when compared to their peers with fewer books, especially for less advantaged populations such as parents with less formal education (Funge et al, 2016). Per the Scholastic (2020) report, frequent readers have greater access to books at home and at school.…”
Section: Access By Other Factorsmentioning
confidence: 99%
“…Wood et al (2020) identified the quiet, safe study space of the library as a haven for students who may not have such conditions at home and which allowed opportunities to engage effectively with literacy, leading to higher confidence and enjoyment of reading and writing outside class. Funge et al (2016) found that children with more books in their homes attain greater academic gains, especially for disadvantaged populations such as low-income families.…”
Section: Access By Other Factorsmentioning
confidence: 99%
“…24 It has been shown that DPIL participants experience increased frequency of reading at home, greater family engagement and interest around books, and a home literacy environment enhanced by the significant number of books delivered. [25][26][27][28] DPIL participants also show evidence of improved skills directly related to kindergarten readiness, namely letter identification, phonologic awareness, and letter naming fluency. [29][30][31] Finally, an urban school district found that DPIL participants scored better on the language and math sections of its validated kindergarten readiness indicator than nonparticipants.…”
mentioning
confidence: 99%
“…Several studies measured reading frequency and found that children enrolled in DPIL programmes read more frequently and for longer periods of time than non-enrolled peers (Funge et al., 2017; Ridzi et al., 2017). Funge et al.…”
mentioning
confidence: 99%
“…Several studies measured reading frequency and found that children enrolled in DPIL programmes read more frequently and for longer periods of time than non-enrolled peers (Funge et al., 2017; Ridzi et al., 2017). Funge et al. (2017) also surveyed the parents of enrolled children and conducted a focus group to explore parent perceptions of the programme’s benefits in an attempt to look beyond kindergarten readiness.…”
mentioning
confidence: 99%